Sticky molecules in not-so-sticky cells. - Hortsch, M.; Bieber, A.J. (Trends in Biochemical Sciences, 1991)
The assignment of specific roles to cell-surface proteins by standard methods can be a major problem. In the technique described below, Schneider-2 (S2) cells, an established Drosophila cell line, have been used in cell transfection and aggregation experiments. As such, they have proved to be a useful tool for the functional characterization of putative cell-adhesion molecules.